Effects of Mating and Social Exposure on Cell Proliferation in the Adult Male Prairie Vole (Microtus ochrogaster). (22nd September 2020) - Castro, A. E.; Young, L. J.; Camacho, F. J.; Paredes, R. G.; Diaz, N. F.; Portillo, W.
Abstract : Microtus ochrogaster is a rodent with a monogamous reproductive strategy characterized by strong pair bond formation after 6 h of mating. Here, we determine whether mating-induced pair bonding increases cell proliferation in the subventricular zone (SVZ), rostral migratory stream (RMS), and dentate gyrus (DG) of the hippocampus in male voles. Males were assigned to one of the four groups: (1) control: males were placed alone in a clean cage; (2) social exposure to a female (SE m/f): males that could see, hear, and smell a sexually receptive female but where physical contact was not possible, because the animals were separated by an acrylic screen with small holes; (3) social exposure to a male (SE m/m): same as group 2 but males were exposed to another male without physical contact; and (4) social cohabitation with mating (SCM): males that mated freely with a receptive female for 6 h. This procedure leads to pair bond formation. Groups 2 and 3 were controls for social interaction. Male prairie voles were injected with 5-bromo-2 ′ -deoxyuridine (BrdU) during the behavioral tests and were sacrificed 48 h later. Brains were processed to identify the new cells (BrdU-positive) and neuron precursor cells (neuroblasts). Our principal findings are that in the dorsal region of the SVZ, SCM and SE m/f and m/m increase the percentage of neuron precursor cells. In the anterior region of the RMS, SE m/f decreases the percentage of neuron precursor cells, and in the medial region SE m/f and m/m decrease the number of new cells and neuron precursor cells. In the infrapyramidal blade of the subgranular zone of the DG, SE m/m and SCM increase the number of new neuron precursor cells and SE m/m increases the percentage of these neurons. Our data suggests that social interaction, as well as sexual stimulation, leads to pair bonding in male voles modulating cell proliferation and differentiation to neuronal precursor cells at the SVZ, RMS, and DG.